PENGARUH KOMPETENSI, PENGEMBANGAN KARIR DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DIVISI PEMASARAN PT. X - FADLILLAH, DERIS; ANANDA, DENTA FELI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study objectives is to analyze the effect of of competency, career development and organizational culture on employee performance in the marketing division at PT. X. This research use saturated sampling technique from 88 respondent as sample of population in marketing division. Hypothesis testing in this is analyzed with linear regression analysis methods. The result of the study shows that employee performance is not affected by competence, while employee performance is affected by career development and organizational culture.